SQUAMOUS CELL CARCINOMA OF THE SKIN: A STUDY OF CLINICOHISTOPATHOLOGICAL CORRELATIONS PREDICTIVE FOR RECURRENCE, METASTASIS AND MORTALITY - Preslav Vasilev; Savelina Popovska; Milen Karaivanov; Dobromir Dimitrov; Ivelina Yordanova (Journal of IMAB, 2023)
Introduction: The incidence of Squamous cell carcinoma of the skin (SCCs) increases annually, and this process will likely be continued because of sun exposure, outdoor activities and the aging population. Objectives: The aim of our study is to analyse clinicohistopathological features, recurrence, metastasis and mortality rates of SCCs in Pleven, Lovech region, Bulgaria. Methods: We investigated 355 patients with histologically confirmed SCCs for the period 2016 – 2022 and carried out a detailed histopathological analysis of 100 tumors. They were divided into two groups according to their macroscopic diameter: with low risk for recurrence and metastases (<20mm) and high – risk (>20mm). We studied the localisation, histological subtype, tumor cell differentiation, microscopic depth of invasion, perineural and lymphovascular invasion, stromal lymphocyte infiltration. Results: We revealed that 73,3% of the patients with SCCs reported severe sunburns, and 1,13% of them underwent immunosuppressive treatment. Head and Neck localisation is the most common – 72,7%. We established a mean histological depth of SCCs of 5,92mm, lymphovascular invasion in 7% and perineural invasion in 5% of the cases. We found that tumors with a macroscopic diameter >20mm have a greater depth of invasion in comparison to SCCs with a smaller diameter. We found an incidence of local recurrence of 4,8%, lymph node metastases at 5,1%, far metastases in internal organs at 2,25% and mortality at 1,97%. Conclusion: Clinicohistopathological features of SCCs with related to recurrence, metastasis and mortality are localisation on the scalp, ears or lips, tumor size >20mm, depth of invasion >6mm, poor tumor cell differentiation, perineural and lymphovascular invasion, low or absent stromal lymphocyte infiltration.